Evolution and plasticity of thermal performance: an analysis of variation in thermal tolerance and fitness in 22 Drosophila species - MacLean, Heidi J. (Philos Trans R Soc Lond B Biol Sci, 2019)
The thermal biology of ectotherms is often used to infer species' responses to changes in temperature. It is often proposed that temperate species are more cold-tolerant, less heat-tolerant, more plastic, have broader thermal performance curves (TPCs) and lower optimal temperatures when compared to tropical species. However, relatively little empirical work has provided support for this using large interspecific studies. In the present study, we measure thermal tolerance limits and thermal performance in 22 species of Drosophila that developed under common conditions. Specifically, we measure thermal tolerance (CT(min) and CT(max)) as well as the fitness components viability, developmental speed and fecundity at seven temperatures to construct TPCs for each of these species. For 10 of the species, we also measure thermal tolerance and thermal performance following developmental acclimation to three additional temperatures. Using these data, we test several fundamental hypotheses about the evolution and plasticity of heat and cold resistance and thermal performance. We find that cold tolerance (CT(min)) varied between the species according to the environmental temperature in the habitat from which they originated. These data support the idea that the evolution of cold tolerance has allowed species to persist in colder environments. However, contrary to expectation, we find that optimal temperature (T(opt)) and the breadth of thermal performance (T(breadth)) are similar in temperate, widespread and tropical species and we also find that the plasticity of TPCs was constrained. We suggest that the temperature range for optimal thermal performance is either fixed or under selection by the more similar temperatures that prevail during growing seasons. As a consequence, we find that T(opt) and T(breadth) are of limited value for predicting past, present and future distributions of species. This article is part of the theme issue ‘Physiological diversity, biodiversity patterns and global climate change: testing key hypotheses involving temperature and oxygen’.